Barriers in Latin America for the management of locally advanced breast cancer - Pinto, JA (2019)
Breast cancer (BC) is a highly prevalent malignancy in Latin American women, most cases being diagnosed at locally advanced or metastatic stages when options for cancer care are limited. Despite its label as a public health problem in the region, Latin American BC patients face several barriers in accessing standard of care treatment when compared with patients from developed countries. In this review, we analyse the landscape of the four main identified barriers in the region: i) high burden of locally advanced/advanced BC; ii) inadequate access to medical resources; iii) deficient access to specialised cancer care and iv) insufficient BC research in Latin America. Unfortunately, these barriers represent the main factors associated with the BC poor outcomes seen in the region. Targeted actions should be conducted independently by each country and as a region to overcome these limitations and create an enhanced model of BC care.